PENERAPAN TEKNIK ICEBREAKER UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATA NAMA SENYAWA DAN PERSAMAAN REAKSI DI KELAS X SMA NEGERI 5 PEKANBARU - Khairiyyah '; Elva Yasmi Amran; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research has conducted on class X SMAN 5 Pekanbaru. The learning process was seriously, rigid, without a sense of excitement, and the state of the learning process at noon during the day, causing student’s bored and tired. Form of research was experimented research with pretest-posttest design Research on the application technique Icebreaker has been done to improve student’s achievement and uppertain of what category of improve student’s achievement on the subject of nomenclature of compounds and chemical equations in class X at SMAN 5 Pekanbaru. The sample consisted of two classes, X.8 class as experiment class and X.3 class as control class that randomly selected after testing normality and homogeneity. Experiment class was treated with implementing technique Icebreaker and the control class was treated without icebreaker technique. Analysis of data used t-test. Data of research obtained tcount > ttable (8,88 > 1,66). The category improvement of student’s achievement in experiment class was high category ( N-Gain = 0,72). It means that using technique Icebreaker can improve student’s achievement on the subject of nomenclature of compounds and chemical equations in class X at SMAN 5 Pekanbaru.Key Words : Icebreaker technique, learning achievement, nomenclature of compounds and chemical equations